'Gabonibacter timonensis' sp. nov., a new bacterium isolated from the human gut of a Pygmy woman. (March 2017) - Bilen, M.; Cadoret, F.; Dubourg, G.; Daoud, Z.; Fournier, P.-E.; Raoult, D.
Abstract: This study supports the main characteristics of a new genus ' Gabonibacter timonensis ' strain Marseille-P3388 (CSUR P3388); a new member of the Gabonibacter genus and Porphyromonadaceae family, that was isolated from a stool sample of a healthy 47-year-old Pygmy woman.